Spain : Safety Net, Bank Resolution, and Crisis Management Framework: Technical Note. (IMF Staff Country Reports; Country Report ;, 2012)
This technical note examines the safety net, bank resolution, and crisis management framework in Spain. The financial safety net architecture for the banking sector comprises the Banco de Espana (BdE), the Fondo de Garantia de Depositos (FGD), and the Fondo de Reestructuracion Ordenada Bancaria (FROB). The note discusses that institutional roles and instruments of the FROB and the FGD need to be realigned. Given the current crisis, authorities should make it a key priority to promptly improve the tools to resolve banks in line with recent international practices.